Fermentasi Pakan Untuk Meningkatkan Produksi Telur Ayam Buras Di Kampus Stiper FB - Liliana Regina Deze; Wigberta Nai Mano; Ludgardis Sebo (CV. SINAR HOWUHOWU, 2026)
Feed formulated to boost egg production in free-range chickens consists of a balanced blend of ingredients designed to meet the birds' nutritional requirements for laying. High-quality feed must contain appropriate levels of carbohydrates, proteins, fats, vitamins, and minerals. In practice, the use of local ingredients can begin by mixing rice bran, corn, and natural concentrates that have been fermented using M4, molasses, and sugar as microbial starters. This process not only enhances digestibility but also reduces the risk of pathogenic microbial contamination and extends the feed's shelf life. Feed fermentation is a processing technique aimed at improving the nutritional value, digestibility, and shelf life of feed ingredients, particularly those sourced locally. The resulting fermented feed is characterized by an aroma reminiscent of *tape* (fermented cassava) or *tempeh*, an absence of rancidity or mold, and a brighter color. With proper planning, local ingredients can serve not merely as an alternative but as a primary component of laying hen feed, especially for small- and medium-scale rural farmers.